GAYA BELAJAR (LEARNING STYLE) BAHASA INGGRIS MAHASISWA SEKOLAH TINGGI PARIWISATA (STP) NUSA DUA BALI DAN IMPLIKASINYA - I Gusti Ngurah Agung Suprastayasa (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2009)
This study aims to identify the EFL learning style preferences of the Students of Sekolah Tinggi Pariwisata Nusa Dua Bali and its implication towards the teaching and learning. A set of questionnaire that was adopted from Riazi & Riasati (2007), comprising of 21 items of students' learning style preferences was administered to 150 first-year students. One hundred and twenty-nine (129) students participated in this study. Results showed the learning style preferences of students i11 different areas and some implications to teaching and learning were discussed.